"I find peace there": how faith, church, and spirituality help mothers of colour cope with postpartum depression. Issue 7 (8th August 2016) - Keefe, Robert H.; Brownstein-Evans, Carol; Rouland Polmanteer, Rebecca
ABSTRACT: This article reports the findings of 30 semi-structured, qualitative interviews with new African American and Latina mothers who have histories of postpartum depression (PPD) to learn how their faith, church participation, and spiritual practices helped them cope with PPD. Six themes emerged: relief from stress, feeling valued and less alone, experiencing gratitude, developing perspective and accepting God's guidance, changing and developing relationships, and preventing self-harm. Specifically, mothers who adhered to their faith beliefs and engaged in spiritual practices described shifts in their perspectives on various life stressors known to contribute to PPD such as negative thoughts and feelings, and strained family relationships, which in turn led them to make positive changes in their lives.